2018
DOI: 10.1016/j.energy.2018.02.135
|View full text |Cite
|
Sign up to set email alerts
|

Fast pyrolysis and steam gasification of pellets prepared from olive oil mill residues

Abstract: Fast pyrolysis and steam gasification of pellets prepared from olive oil mill residues. Energy, Elsevier, 2018, 150, pp.a b s t r a c t This paper examines the fast pyrolysis coupled with the steam gasification of agropellets prepared from the olive oil industries by-products via Macro-thermogravimetry. Three pellets samples were prepared from exhausted olive mill solid waste, impregnated olive mill wastewater/exhausted olive mill solid waste and impregnated olive mill wastewater/pine sawdust. The behavior of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
19
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 38 publications
4
19
2
Order By: Relevance
“…9 and confirmed in Table 3 (the characteristic time is approximately 4.92 10 À3 s À1 ), while the highest one is obtained by EOMSW-OMWW powder (approximately 9.80 10 À3 s À1 ). However, we notice that these values are higher than those reported in the literature under the same experimental conditions [39]. Indeed, in agreement with many published results in the literature, the blended and impregnated samples experience the highest gasification rates thanks to the mineral contents supplied by the OMWW as it is shown in Table 2 [4,11,26,32,39e41].…”
Section: Influence Of the Samples' Properties On The Gasification Reasupporting
confidence: 91%
See 3 more Smart Citations
“…9 and confirmed in Table 3 (the characteristic time is approximately 4.92 10 À3 s À1 ), while the highest one is obtained by EOMSW-OMWW powder (approximately 9.80 10 À3 s À1 ). However, we notice that these values are higher than those reported in the literature under the same experimental conditions [39]. Indeed, in agreement with many published results in the literature, the blended and impregnated samples experience the highest gasification rates thanks to the mineral contents supplied by the OMWW as it is shown in Table 2 [4,11,26,32,39e41].…”
Section: Influence Of the Samples' Properties On The Gasification Reasupporting
confidence: 91%
“…Note that under similar experimental conditions, Guizani et al [10] show that for a conversion (X) of 90%, and at a temperature of 900 C, the gasification rate of beech wood chips is approximately 15 10 À3 s À1 . However, our obtained values are lower than those found by Guizani et al [10], but higher than those reported by Lajili et al [39].…”
Section: Influence Of Temperature and Steam Molar Fraction On The Chacontrasting
confidence: 82%
See 2 more Smart Citations
“…Complete combustion of a fuel occurs if there is sufficient oxygen supply. However, this process is not economically friendly due to the low efficiency of the combustion process and high production of emissions in particles and gas form [12]. Biomass pyrolysis is one of the most efficient technologies to produce biofuels.…”
Section: Introductionmentioning
confidence: 99%